Hydropower and irrigation development in the Omo Valley. Development for whom? - Turton, David (Antropologia Pubblica, 2018)
The Gibe III Dam and its associated irrigation development in Ethiopia’s Omo Valley constitute a textbook example of how not to do river basin development. Having ignored years of research findings on the impacts of development-forced displacement and resettlement, the politicians and planners are in danger of presiding over a social and environmental disaster of historic proportions. Hundreds of thousands of people, mainly agro-pastoralists living in the Lower Omo and around Lake Turkana in Kenya, stand to lose vital resources that make up the basis of their current livelihood system without consultation and without compensation. The result is bound to be long term impoverishment and increased morbidity and mortality amongst those affected. Meanwhile, the extent of irrigation development planned for the Lower Omo will drastically reduce the volume of Lake Turkana, the world’s largest desert lake. But it is not too late to take some basic steps that would at least reduce the worst extent of these impacts and thereby help to reconcile economic development with social justice. Most important of all would be a well targeted and well funded programme of compensation and long-term benefit sharing.